Purification, crystal structure and properties of azoxytriazolone (AZTO) - Zhou, Tianlong; Gong, Jiaxu; Xie, Mingzhen; Wang, Bozhou; Jiang, Yifan; Wang, Jiaheng; Zhou, Jie; Zhong, Linzhi; Dai, Yatang (FirePhysChem (Online), 2023)
•The separation and purification of AZTO was achieved for the first time by a simple salt formation reaction.•The high purity AZTO shows excellent thermal stability (Tdec = 352 °C).•AZTO exhibits a high crystal density of 1.902 g/cm3 at 193 K. In this work, the azoxytriazolone (AZTO) was synthesized by electrochemical reduction 5-nitro-1,2,4-triazol-3-one (NTO) under different types of electrolytes which were Na2SO4 and H2SO4. By comparing the yield of AZTO/azoTO synthesized under different electrolyte conditions, the work found that sulfuric acid as the electrolyte has a positive effect on the synthesis of AZTO. On this basis, the high-concentration AZTO was prepared by regulating the concentrations of sulfuric acid (0.05M, 0.1M, 0.5M, 1M). Finally, by introducing an appropriate amount of NaOH, we successfully achieved the separation and purification of AZTO from the mixture of AZTO and azoTO. In addition, single crystal AZTO was also prepared in this experiment to test its crystal structure, which illustrated that the crystal density of AZTO is 1.902 g/cm3 at 193 K, belonging to the monoclinic crystal system with space group P21/n. The thermal properties results of AZTO showed that the thermal stability properties of AZTO were affected by AZTO/azoTO ratio, and the thermal decomposition peak of pure AZTO is 352°C when the content of azoTO is zero. On the contrary, the BAM susceptibility tester test demonstrated the impact susceptibility is 30 J and the friction susceptibility is greater than 360 N of AZTO, which are unaffected on azoTO. According to the K-J empirical formula, the blasting velocity and detonation pressure of AZTO were 7713.5 m/s and 26.1 GPa, respectively. The influences of different types of electrolytes and sulfuric acid concentrations on the yield of AZTO were evaluated, and the relevant reaction mechanism of electrochemical synthesis of AZTO and azoTO was supplemented in this paper. [Display omitted]